2016
DOI: 10.21767/2386-5180.1000105
|View full text |Cite
|
Sign up to set email alerts
|

Medium Chain Triglyceride Oil: An Intended Placebo with Unexpected Adverse Effects

Abstract: Background: Medium chain triglyceride (MCT) oil is a synthetic oil made from medium chain C8 and C10 fatty acids. It has been traditionally used as a neutral "placebo" in lipid clinical trials. Thus, we had selected MCT oil capsules as a placebo, intended for comparison with an omega-3 polyunsaturated fatty acid containing supplement, to measure fatty acid profiles and inflammation in healthy people. Methods:The trial was a double-blinded, randomized, placebo controlled trial with cross-over, 4 weeks each stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Both these fatty acids are important from the physiological point of view [30]. A similar effect of MCT was found in human blood by Fergusson et al [31]. Jean and Chiang [32] fed sows with MCT and found that it could be an effective means of increasing the survival of neonatal pigs.…”
Section: Effect Of Oils In Maternal Feeding On the Sows Reproductive supporting
confidence: 55%
“…Both these fatty acids are important from the physiological point of view [30]. A similar effect of MCT was found in human blood by Fergusson et al [31]. Jean and Chiang [32] fed sows with MCT and found that it could be an effective means of increasing the survival of neonatal pigs.…”
Section: Effect Of Oils In Maternal Feeding On the Sows Reproductive supporting
confidence: 55%
“…However, there is also some in vitro evidence that MCT can downregulate adiponectin mRNA expression in adipocytes in the presence of TNF-alpha [60]. Supplementation with n-3 long chain polyunsaturated fatty acids has been associated with an increase in adiponectin [61], and supplementation with MCT has been associated with a decrease in eicosapentaenoic acid (EPA) and docosapentaenoic acid (DHA) [62]. We did not measure changes in EPA and DHA, although this may represent a potential mechanism for the decrease in total adiponectin that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D 3 absorption was significantly higher with peanut oil than with MCTs in both fasting and non-fasting states [113]. For this reason, and because MCT appeared to also affect the fatty acid levels, MCT was not used as a control supplement in the trial with CD participants and a refined fish oil was used instead [37].…”
Section: Vitamin Dmentioning
confidence: 99%